CRIMINAL LIABILITY FOR ANIMAL CRUELTY (COMPARATIVE RESEARCH) - Лихова, Софія Яківна; Майстро, Діана Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to study the experience of foreign countries on criminal liability for animal cruelty. Research methods: the methods used are dogmatic, comparative-legal, system-structural, functional and statistical. Results: it has been established that the faunistic legislation of countries such as the Republic of Poland, the Federal Republic of Germany and the Republic of France can be considered for the implementation of these norms in domestic law. Discussion: the issue of criminal liability for animal cruelty in domestic criminal law should not be considered as sufficiently investigated. Considering the European Convention for the Protection of Animals of 13 November 1987, it should be noted that this is the first detailed regulation on the safeguarding of the normal existence of not individually vulnerable or economically valuable animals, but of companion animals, the most frequently abused human abusers. On the other hand, it is a document that directly addresses the value of the life and well-being of each animal. This Convention sets out the basic principles of keeping, breeding and training animals, and sets age restrictions for owners to purchase and keep pets. Studying the legislation of certain foreign countries, especially those in whose legislation this problem is practically solved (the Republic of Poland, the Federal Republic of Germany and the Republic of France) gives the opportunity to reach specific conclusions and make author's recommendations on the improvement of the domestic criminal legislation. The analysis of the criminal legislation of Ukraine shows that the protection of animals from ill-treatment of animals is insufficiently taken into account and requires the study of this issue through the use of foreign experience whose criminal legislation contains practically perfect standards for the protection of animals.